PENGARUH INTEGRITAS DAN OBEJEKTIVITAS TERHADAP KINERJA AUDITOR DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA BPKP PERWAKILAN PROVINSI MALUKU) - Saputra, Rivano Amin; Anakotta, Fanny Monica; Atarwaman, Rita J. D. (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine, analyze and test the effect of integrity on auditor performance. To find out, analyze and test the effect of objectivity on auditor performance. To find out how to analyze and test organizational culture to moderate the effect of integrity on auditor performance. To find out how to analyze and test organizational culture to moderate the effect of objectivity on auditor performance. This research was at the BPKP office representing Maluku province. The sample in this study were 42 auditors. This research approach uses descriptive quantitative. This study uses data analysis methods using SPSS version 26 which runs on computer media. In this study the research instrument used was a questionnaire or questionnaire. The variable measurement scale used in this study is the Likert scale. The results of this study indicate that the integrity variable affects auditor performance, objectivity influences auditor performance, organizational culture moderates the effect of integrity on auditor performance, organizational culture moderates the effect of objectivity on auditor performance.